2018
DOI: 10.1152/jn.00331.2017
|View full text |Cite
|
Sign up to set email alerts
|

Escape from homeostasis: spinal microcircuits and progression of amyotrophic lateral sclerosis

Abstract: In amyotrophic lateral sclerosis (ALS), loss of motoneuron function leads to weakness and, ultimately, respiratory failure and death. Regardless of the initial pathogenic factors, motoneuron loss follows a specific pattern: the largest α-motoneurons die before smaller α-motoneurons, and γ-motoneurons are spared. In this article, we examine how homeostatic responses to this orderly progression could lead to local microcircuit dysfunction that in turn propagates motoneuron dysfunction and death. We first review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 197 publications
(252 reference statements)
1
58
0
Order By: Relevance
“…It has been demonstrated that once the fatiguing muscle cannot satisfy the force generating demand from intrinsic changes, then the excitability of the motoneuron pool could be facilitated by the afferent feedback [23,24]. Brownstone et al [25] theorized that the facilitation of the premotor circuits on γ-MNs would contract the intrafusal muscle fibers out of proportion. Furthermore, focusing attention on a task secondary to any perceived weakness also increases muscle spindle sensitivity [26].…”
Section: Primary Damage Phase: Acute Compression Axonopathy and Possimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that once the fatiguing muscle cannot satisfy the force generating demand from intrinsic changes, then the excitability of the motoneuron pool could be facilitated by the afferent feedback [23,24]. Brownstone et al [25] theorized that the facilitation of the premotor circuits on γ-MNs would contract the intrafusal muscle fibers out of proportion. Furthermore, focusing attention on a task secondary to any perceived weakness also increases muscle spindle sensitivity [26].…”
Section: Primary Damage Phase: Acute Compression Axonopathy and Possimentioning
confidence: 99%
“…It has been shown that sustained submaximal isometric contraction ultimately leads to a progressive decline in the discharge of muscle spindle afferent [27]. According to the theory of Brownstone et al [25], the increased premotor activity and the concomitant spindle afferent input will eventually end in an escape from homeostasis in amylotrophic lateral sclerosis. We propose that the above excessive coinciding mechanical and metabolic insults impair the energy supply of the mitochondria in the sensory terminals of the muscle spindle, and this energy deficiency eventually leads to an escape from homeostasis, which we call DOMS.…”
Section: Primary Damage Phase: Acute Compression Axonopathy and Possimentioning
confidence: 99%
“…In fact, as discussed in more detail in the Section Astrocyte GluR as a Potential Pre-onset ALS Treatment Target, motoneurons are mathematically and functionally more susceptible to such instability (Mitchell and Lee, 2012; Irvin et al, 2015). Other recent work has also illustrated that motoneuron microcircuits are more prone to homeostatic dysregulation (Brownstone and Lancelin, 2018). Given the large variance in experimental data, small changes that were statistically insignificant may actually be physiologically significant to ALS cells.…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with that observation, reducing Ia proprioceptive muscle spindle afferents partly contributed to ␣-MN survival. Therefore, identification and characterization of circuit-specific vulnerability to disease progression in ALS (Brownstone and Lancelin, 2018) could help develop effective therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%